(untitled) (Madison, Wis., 1968)
Proceedings of a symposium sponsored and financed by the Tennessee Valley Authority and the American Potash Institute and cosponsored by the American Society of Agronomy, Crop Science Society of America, and Soil Science Society of America, and held at the National Fertilizer Development Center, TVA, Muscle Shoals, Alabama, June 18-19, 1968."
Keywords: Potassium fertilizers,Potassium in agriculture,Soils,Plants; Potassium content,Effect of potassium on